KNOWLEDGE, ATTITUDE AND SKILLS OF NURSING STUDENTS REGARDING EVIDENCE BASED PRACTICE IN TERTIARY HOSPITALS - JOHN , Y; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Evidence-based practice (EBP) is essential for improving healthcare outcomes by integrating clinical expertise, patient preferences, and research evidence. However, the adoption of EBP remains challenging, particularly in developing countries like Pakistan. Objective: To assess the knowledge, attitudes, and skills of nursing students regarding EBP in tertiary hospitals in Pakistan. Methods: A descriptive cross-sectional study was conducted among 150 nursing students using purposive sampling. Data were collected through a validated questionnaire and analyzed using SPSS version 26. Descriptive statistics were used to summarize demographic variables and EBP-related responses. Results: The majority of participants (46.2%) were aged 26-30 years, and most held a BSN qualification (43.1%). Knowledge about EBP was limited, with only 28.5% correctly defining it and 46.9% recognizing clinical practice guidelines as the most useful knowledge source. Attitudes were predominantly negative, with only 26.2% agreeing that EBP aids clinical decision-making. Skills assessment revealed that while 66.2% were confident in evaluating scientific articles, only 34.5% could formulate clinical questions for evidence searching. Conclusion: The findings highlight substantial gaps in EBP-related competencies among nursing students in Pakistan. Curriculum enhancements, mentorship programs, and improved access to research resources are urgently needed to address these deficiencies and promote the integration of EBP into nursing practice.